Revitalizing numeracy literacy: transforming learning instruments through virtual reality-based worksheet design - Ayu Dwi Setiorini, Putri; Muinah (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Purpose: This study analyzes student perceptions regarding the design of Virtual Reality (VR)-based mathematics worksheets, aimed at mitigating affective, cognitive, and media-related disparities inherent in conventional intruction. It addresessed a critical literature gap by identifying user-centered design parameters for immersive technology specifically tailored for secondary education. Methodology: Employing a qualitative approach, the research involved six students from MAN 1 North Lampung, selected through stratified sampling based on cognitive proficiency levels. Data were gathered via semi-structured interviews and subjected to rigorous analysis using the Miles and Huberman interactive model to ensure interpretative validity. Findings: The findings confirm highly positive student perceptions and establish three fundamental design pilar: contextual narrative, gamification mecchanisms, and a moderate task volume (5-10 items). These elements function as catalyst for matematical literacy by enhancing students’ capacity to interpret visual information and fostering active learning engagement. Practical implications: These result provide a strategic benchmark for educators and curriculum designers to transform static instructional materials into immersive, adaptive media aligned with the cognitif and behavioral characteristics of the digital generation. Originality/value: The primary significance of this research lies in the proposal of a tripartite solution framework (affective-cognitive-media) through VR integration, providing empirical evidence that immersive technology can spesificcally circumvent contextual and motivational berriers in mathematics educcation. Tujuan: Studi ini menganalisis persepsi siswa mengenai desain lembar kerja matematika berbasis Virtual Reality (VR), yang bertujuan untuk mengurangi kesenjangan afektif, kognitif, dan terkait media yang melekat pada pengajaran konvensional. Studi ini mengatasi kesenjangan literatur yang kritis dengan mengidentifikasi parameter desain yang berpusat pada pengguna untuk teknologi imersif yang secara khusus disesuaikan untuk pendidikan menengah. Metodologi: Dengan menggunakan pendekatan kualitatif, penelitian ini melibatkan enam siswa dari MAN 1 Lampung Utara, yang dipilih melalui pengambilan sampel bert stratified berdasarkan tingkat kemampuan kognitif. Data dikumpulkan melalui wawancara semi-terstruktur dan dianalisis secara cermat menggunakan model interaktif Miles dan Huberman untuk memastikan validitas interpretatif. Hasil: Temuan mengkonfirmasi persepsi siswa yang sangat positif dan menetapkan tiga pilar desain fundamental: narasi kontekstual, mekanisme gamifikasi, dan volume tugas yang moderat (5-10 item). Unsur-unsur ini berfungsi sebagai katalisator untuk literasi matematika dengan meningkatkan kemampuan siswa untuk menafsirkan informasi visual dan mendorong keterlibatan pembelajaran aktif. Implikasi praktis: Hasil ini memberikan tolok ukur strategis bagi pendidik dan perancang kurikulum untuk mengubah materi pembelajaran statis menjadi media imersif dan adaptif yang selaras dengan karakteristik kognitif dan perilaku generasi digital. Orisinalitas/nilai: Signifikansi utama penelitian ini terletak pada usulan kerangka solusi tiga bagian (afektif-kognitif-media) melalui integrasi VR, yang memberikan bukti empiris bahwa teknologi imersif secara khusus dapat mengatasi hambatan kontekstual dan motivasional dalam pendidikan matematika.